Awareness of the Ward Based Outreach Team and the services offered by the programme in the Tshwane health district, South Africa - T. Bongongo; J. V. Ndimande; G. A. Ogunbanjo; A. T. Masango-Makgobela; S. N. Nyalunga; I. Govender (South African Family Practice)
Background: The Ward Based Outreach Team (WBOT) is an organised team approach to a healthcare system based on the principles of epidemiology, primary health care, preventive medicine and health promotion. Globally, it has become a primary care response to many health challenges such as universal health coverage. The beneficiaries are community members, also referred to as households. Methods: The study assessed the awareness of the WBOT and the services offered by the programme in the Tshwane health district of South Africa. This was a cross-sectional survey conducted in all seven sub-districts of the health district. The health district is further sub-divided into 150 health wards. Eighty-five health wards were randomly selected for the study. Using the sample size calculator, with a confidence interval of 5% and confidence level of 99%, the sample size of participants was 654. However, during the data collection process there was over-sampling of up to 764. Participants were recruited by convenience sampling. Data were collected between October 12 and December 3, 2015, using a pre-piloted, structured questionnaire administered by 14 trained field workers. Results: The study obtained 6 288 responses from the 764 participants. The responses were grouped into two sections, ‘Yes’ and ‘No’. A summary of the responses showed that the number of ‘yes’ responses, the number of participants who were aware of the WBOT and the services offered by the programme were higher than the number of participants who were unaware of the programme. The figures were 5 590 (88.8%) ‘yes’ responses and 698 (11.1%) ‘no’ responses. Conclusion: In summary, the awareness of the WBOT and the services offered by the programme in the Tshwane health district, South Africa is evaluated to be 88.8%.